ANALISIS HUBUNGAN FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN PETERNAK SAPI PERAH PADA KOPERASI SUSU DI KABUPATEN SEMARANG - Dinar Anindyasari; Agus Setiadi; Mukson Mukson (Universitas Mulawarman, 2019)
This study aimed to determine the level of income earned by farmers and identify factors - factors that affect the income of dairy farmers Dairy Cooperative members in Semarang District. The method used in this study was a survey. Method of determining the milk cooperatives and sample summit conducted by purposive sampling. Descriptive data analysis and statistics. The results of the research that the level of income is positive with income farmers cooperative members Andini Luhur Rp. 1,251,638.28 / month and the income of farmers cooperative members Revelation Supreme Rp. 1,154,190.62 / month. Value profitability of 67.92% and 57.37%, where the value is more than the interest rate on deposits of 6%.